Number theory in secondary schools’ mathematics - Stankus, Eugenijus (Lietuvos matematikos rinkinys, 2021)
Schools’ curricula are analyzed in terms of Number Theory. We deduce, that the concept of number is first and main in secondary schools’ Mathematics. The problems of divisibility of numbers are also discussed, the examples of such problems are given.